IMPLEMENTASI RESOLUSI MICRO CONFLICT BERBASIS ALTERNATIVE DISPUTE RESOLUTION (Studi Peran Mediasi di Pusat Pelayanan Terpadu Perempuan dan Anak Korban Kekerasan ‘Rekso Dyah Utami’ Yogyakarta) - Linda Evirianti (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Humans are social beings formed by mutual interests within the scope of the community. In relation to such reciprocity, social phenomena often arise in the form of violence or conflict arising from the existence of different interests, so that with the emergence of conflicts or disputes, the law plays an important role in resolving these conflicts, especially acts of violence against women and children. Through the Rekso Dyah Utami agency, there is an effort to minimize an act of violence. The way it is done is through the assistance of mediators in resolving cases that occurred at Integrated Service Center for Women and Children of Violence Victims (P2TPAKK) Rekso Dyah Utami through mediation practice.Keywords: communication transaction (transactional analysis), mediation, mediator.